Terahertz wave generation and detection in double-graphene layered van der Waals heterostructures. (14th October 2016) - Yadav, Deepika; Tombet, Stephane Boubanga; Watanabe, Takayuki; Arnold, Stevanus; Ryzhii, Victor; Otsuji, Taiichi
Abstract: We report on the first experimental observation of terahertz emission and detection in a double graphene layered (GL) heterostructure which comprises a thin hexagonal-boron nitride tunnel-barrier layer sandwiched between two separately contacted GLs. Inter-GL population inversion is induced by electrically biasing the structure. Resonant tunneling and negative differential resistance is expected when the two graphene band structures are perfectly aligned. However, in the case of small misalignments we demonstrate that the photon-absorption/emission-assisted non-resonant- and resonant-tunneling causes all excess charges in the n-type GL to recombine with the holes in the p-type GL giving rise to an increased measured dc current. This work highlights a novel strategy for the realization of efficient voltage-tunable terahertz emitters and detectors.